On Possible Models of Language - Karpovas, Leonidas (Problemos, 1975)
In the first part of the paper the author deals with the logical basis of linguistic modelling. A starting point of our discussion is a notion of theory (in the mathematical sense). A theory may be regarded as an inductive class of elementary propositions. Further, we believe that there is a class of models for the theory. First of all, we define abstract models to be an interpreted theory, i.e., a theory with grammatical categories assigned to its elements as their meaning. The ontological model is a natural language itself. In the second part of the paper two types of transformational (generative) rules are introduced.